MORPHOLOGICAL DESCRIPTION OF DESI CHICKEN IN MINICOY, LAKSHADWEEP ISLANDS - M.S. Ajina; T. Sujatha; Y. Gladson; E.B. Chakurkar; A.K. De; Jai Sunder; D. Bhattacharya (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A morphological characterization study was conducted on desi chicken at Minicoy in Lakshadweep Islands. The phenotypic characters such as colour and pattern of plumage, comb type and colour of skin, earlobe and shank were documented in both male and female adult chickens as per the guidelines of National Bureau of Animal Genetic Resources (NBAGR). The desi chicken from Minicoy Islands are smaller in size with a short beak, and exhibit a striking multicolour plumage intricately speckled across its body feathers, tail and neck. Significant sexual dimorphism was noted for the phenotypic characters. A total of 3 cocks and 7 hens were reported with different combination of plumage colours and patterns. The study indicated that these desi birds have distinct morphological characters that is worth for further investigation.